Analysis of novel whispering gallery mode cavity - Zhu, Di (2013)
Whispering gallery mode (WGM) is formed when light is trapped inside a circular resonator by continuous total internal reflections. Due to its small mode volume and high quality-factor, WGM has been intensively studied and widely adopted for applications such as sensing, filtering and lasing. Normally, WGM tends to stay near the outer surface of the resonator with a penetration depth no larger than several wavelengths. In this project, in order to enhance the field penetration, we propose a radially graded index WGM cavity design with index profile n=b/r, where n is the refractive index, b is a constant and r is the radial position. The design principle is to gradually increase the refractive index along the radial direction towards the center of the resonator. As a result, the externally coupled light will bend towards the higher index region, i.e. the center of the resonator. The analysis in this report is based on a tubular WGM cavity, which is the commonly adopted liquid core optical ring resonator (LCORR) configuration. With the proposed index profile, the cladding imposes no potential barrier and allows externally coupled evanescent wave to penetrate freely. This design has direct impact on the improvement of the current LCORR, and promises the future implementations of novel liquid-based WGM devices.